Windows XP networking - Cohen, Kackie (Addison-Wesley, 2005)
Windows XP: practical solutions for working network administrators Deploying, managing, or supporting networks with Windows XP clients? Here's all the information you need to maximize reliability, security, and performance...and minimize hassles and aggravation! Kackie Cohen and Andrew Daniels share the extraordinary experience they've gained deploying and running some of the world's largest Windows networks. They don't waste time on the "basics" you already know. Rather, they focus on the specific challenges you face as a working professional. You'll find best practices and real-world tips for everything from authentication to Internet connectivity, firewalls to wireless networking...and a whole lot more.Coverage includes: *Security best practices: system hardening, access control, authentication, authorization, and VPNs *LANs in depth: TCP/IP configuration, heterogeneous networking, services for Unix, and more *Wireless networking configuration and features, including Windows XP's new UPnP support *Internet connection firewall and Internet connection sharing: step-by-step configuration and management recommendations *Mobile/remote networking, including dial-up and remote access services *Saving money with Windows XP's new IP telephony and conferencing features *QoS: prioritizing network traffic to improve mission-critical application performance *Troubleshooting: network diagnostics, remote assistance, utilities, service packs, and command-line tools *Includes extensive coverage of Windows XP Professional clients